The diversity of plant species in the ecotourism zone of Gunung Leuser National Park, Tangkahan, Indonesia - Deliana Febrianti; Muhammad Dandi Harisandy; Adi Bejo Suwardi (Jurnal Biologi Tropis, 2022)
Gunung Leuser National Park (TNGL) is one of Indonesia's conservation areas, serving as a haven for various plants and animals. The ecotourism zone is a part of the utilization zone in the GLNP area that is intended for the development of ecotourism and has a high diversity of plant species. However, information concerning the potential of plants in the GLNP's ecotourism zone has not been widely disseminated. The present study aims to inventory plant species in Gunung Leuser National Park's ecotourism zone. The exploration method was used in this study, which lasted from November to December 2021. A total of 47 plant species from 30 families were discovered in the study area, with Apocynaceae, Euphorbiaceae, Fabaceae, Lamiaceae, and Solanaceae having the most species. These plants have a variety of uses, including food, spices, ornamental plants, and materials for traditional/ritual ceremonies.